Premis Internacionals Barcelona '92. (Barcelona : Olimpiada Cultural, 1992)
Gaudi, Antoni ; Casals, Pau ; Monturiol, Narcis ; Miro, Joan ; El Brusi ; Samaranch, Joan Antoni
Premis Internacionals Barcelona '92, Olimpiada Cultural, Barcelona, 1992
boek